Mindfulness and metacognition in facing with fear of recurrence: A proof‐of‐concept study with breast‐cancer women. Issue 3 (6th February 2019) - Cheli, Simone; Caligiani, Lucia; Martella, Francesca; De Bartolo, Paola; Mancini, Francesco; Fioretto, Luisa
Abstract: Objective: Fear of recurrence is a crucial issue in cancer care. On the one hand, the increase of cancer‐survival rates and complexity of care is exposing patients to this type of fear. On the other hand, it is a distressing and recurrent psychosocial risk that affects quality of life and adherence to follow‐up. Patients should have access to targeted psychological interventions aimed at reducing or preventing fear of recurrence. This mixed‐methods pilot study reports the preliminary results of a novel mindfulness‐ and metacognition‐based intervention specifically targeting fear of recurrence. Methods: The study was composed of an individual (n = 76) and a group (n = 38) intervention, both lasting 8 weeks, that were evaluated through a preassessment and postassessment and a 1‐month follow‐up. We enrolled women recovering from breast cancer (n = 114) in follow‐up care, with significant psychosocial distress. Patients with more severe psychopathology were assigned to the individual treatment, whereas the less severe ones were assigned to the group treatment. We explored the distress and the fear of recurrence through standardized measures and in‐depth qualitative interviews. Results: Results showed that depressive, anxious, and post‐traumatic symptoms were reduced significantly in the entire sample. Patients reported a significant reduction of fear of recurrence, which was described in terms of loss of control, increase of uncertainty, and decrease of metacognitive and interpersonal skills. Conclusions: Although further studies are needed, these findings provide preliminary proof‐of‐concept results for the potential of integrated mindfulness‐ and metacognition‐based interventions to reduce fear of recurrence in cancer patients.